1968
DOI: 10.1159/000129988
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the male meiosis of <i>Ellobius lutescen</i><i>s</i> Th.

Abstract: Studies were carried out on the male meiosis of Ellobius lutescens. The testicles of 29 male specimens were used for this purpose. Among 100 pachytene figures, 25 revealed an association between the sex vesicle and an autosomal bivalent of medium size, whereas in 75 figures the sex vesicle appeared as an isolated structure. The importance of this finding in relation to the proposed translocation of a segment of the Y chromosome to an autosome as well as the significance of this event in relation to a mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…An association with an autosomal bivalent during male meiosis has been observed in about 25 % of the pachytene figures examined; 75 % of the sex vesicles remained as univalent (Castro-Sierra and Wolf, 1968). From these observations it was concluded that the missing Y chromosome is translocated to an autosome where the single X chromosome forms a pseudo-trivalent with the shared sequences of a putative pseudoautosomal region.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…An association with an autosomal bivalent during male meiosis has been observed in about 25 % of the pachytene figures examined; 75 % of the sex vesicles remained as univalent (Castro-Sierra and Wolf, 1968). From these observations it was concluded that the missing Y chromosome is translocated to an autosome where the single X chromosome forms a pseudo-trivalent with the shared sequences of a putative pseudoautosomal region.…”
mentioning
confidence: 92%
“…It was assumed that the testis-determining part of the Y chromosome had been translocated to the X or to one of the autosomes or that the tiny Y chromosome was too small for routine detection by cytogenetic studies (Castro-Sierra and Wolf, 1968). The odd chromosome 9 represents the single X chromosome in the "weird" species Ellobius lutescens.…”
mentioning
confidence: 99%
“…Hence, the original hypothesis by Matthey (1953;1958) and White (1957) was refuted and instead a Y autosome translocation proposed to explain the sex chromosome constitution in this species (Castro-Sierra and Wolf, 1967). The latter hypothesis got additional support from an association between the sex vesicle and an autosomal bivalent in a proportion of cells in male meiosis (Castro-Sierra and Wolf, 1968). However, the translocated Y was undetectable by the cytogenetic techniques of that time.…”
mentioning
confidence: 97%
“…3) showed the odd chromosome to be early replicating together with the autosomes in both, males and females. Detailed studies on the male meiosis of Ellobius lutescens suggested also that the odd chromosome represents a standard type, single mammalian X chromosome (Castro-Sierra and Wolf, 1968). Hence, the original hypothesis by Matthey (1953;1958) and White (1957) was refuted and instead a Y autosome translocation proposed to explain the sex chromosome constitution in this species (Castro-Sierra and Wolf, 1967).…”
mentioning
confidence: 99%
“…The X remains un paired at meiosis. Meiosis and spermatogenesis are maintained without a Y chromosome (Castro-Sierra and Wolf, 1968;Chandra, 1999). The mammalian sex-determining gene SRY is absent in XO species of Ellobius (Kuroiwa, 2012).…”
Section: Geneticsmentioning
confidence: 99%